Pengaruh Nasionalism (Nasionalisme) dan Trust (Kepercayaan Pada Pemerintah) terhadap Kepatuhan Wajib Pajak Orang Pribadi - Siti Nuridah; Joelianti Dwi Supraptiningsih; Rony Marthin Sitohang; Listya Ningrum; Maulana Fahmi Muzaqi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
National development in order to make Indonesia a developed country continues to be carried out, to make this happen, funding is needed, one of which comes from taxes. As good Indonesian citizens, taxpayers have a high sense of nationalism and trust in the government which can increase taxpayer compliance in fulfilling their obligations. The taxpayer compliance ratio from 2016-2021 has increased every year but has not yet reached 100%. The method used is the analytical method. quantitative, determining the sample using a quota sample with a sampling technique using an incidental technique, for the population of individual taxpayers at KPP Pratama North Cikarang. There is an influence of nationalism on taxpayer compliance at KPP Pratama North Cikarang with t calculated (18.289) greater than t table (1.984) so ​​H1 is accepted, there is an influence between trust on taxpayer compliance at the North Cikarang Pratama KPP with t calculated (9.219) greater than t table (1.984) so ​​H2 is accepted, there is an influence between nationalism and trust together on compliance individual taxpayer with calculated F (168,650) greater than F table (3,090). KPP Pratama North Cikarang needs to increase the sense of nationalism and trust of taxpayers so that tax compliance will increase.